Juridical Review of the Legal Position of Employment Relations Without A Written Employment Agreements - Anak Agung Sagung Ngurah Indradewi; Ni Luh Ade Krisnatalingsih (Law Doctoral Community Service Journal, 2022)
The employment agreement is the beginning of a working relationship between workers, laborer and the entrepreneur. A work agreement is an agreement where the worker-labor party binds to work on the part of the employer. Work agreements can be made into written or oral form. Work agreements made in oral form do not conflict with the provisions of Law Number 13 of 2003 concerning Employment, i.e. contained in the provisions Article 51 paragraph 1, i.e. employment agreements are made in writing or verbally. The type of research used in this study is normative legal research (normative law research) which uses a normative case study in the form of a review of the Law. The source of legal material used in this study came from primary legal material source and secondary legal material. In this disclaimer the author uses a comprehensive legal analysis in reviewing the legal substance associated with the discussion. The legal position of employment relations without a written employment agreement based on the perspective of labor law has a strong, legal position as long as it does not conflict with the legal conditions of the employment agreement, as provided for in Article 52 paragraph (1) of Law Number 13 of 2003 concerning Employment. As a result of the law of employment without a written employment agreement, if the type of employment agreement is a Specific Time Work Agreement (PKWT) made in oral form, then the status changes to an Unspecified Time Work Agreement (PKWTT) and if the type of employment agreement is an Unspecified Time Work Agreement (PKWTT) then the employer is obliged to issue a letter of appointment to the worker/labor concerned to become a permanent worker. Verbal work agreements have not been able to provide full legal protection to workers, potentially harming workers and workers to the fulfillment of their rights and obligations as workers.